An invasive fish promotes invasive plants in Minnesota lakes. (21st May 2020) - Larkin, Daniel J.; Beck, Marcus W.; Bajer, Przemyslaw G.
Abstract: Biological invasions can greatly alter ecological communities, affecting not only the diversity and abundance but also composition of invaded assemblages. This is because invaders' impacts are mediated by characteristics of resident species: some may be highly sensitive to invader impacts while others are unaffected or even facilitated. In some cases, this can result in invasive species promoting further invasions; in particular, herbivory by introduced animals has been shown to disproportionately harm native plants, which can indirectly benefit non‐native plants. Here, we investigated whether such patterns emerged through the effects of an invasive fish species on lake plant communities. Specifically, we tested whether invasion of Minnesota (U.S.A.) lakes by Cyprinus carpio (common carp), an omnivorous, benthivorous fish known to reduce abundance and richness of aquatic plants, differentially affected native versus non‐native plant species. We applied statistical models to a large, long‐term monitoring dataset (206 macrophyte taxa recorded in 913 lakes over a 20‐year time period) to test whether carp altered community composition, to identify which macrophyte species were most sensitive to carp and determine whether species characteristics predicted carp sensitivity, and to characterise consequences of carp invasion on lake‐level vegetation attributes. We found that carp exerted strong selective pressure on community composition. Native macrophytes, those with a more aquatic growth form, and those considered less tolerant of disturbance (i.e. higher coefficients of conservatism) were more sensitive to carp. Conversely, no introduced macrophytes exhibited sensitivity to carp and all had higher probabilities of occurrence as carp abundance increased. The net effect of carp invasion was a shift toward less species‐rich plant communities characterised by more non‐native and disturbance‐tolerant species. These results have several implications for conservation and management. First, they reinforce the need to prevent further spread of carp outside of their native range. Where carp have already established, their control should be incorporated into efforts to restore aquatic vegetation; this may be an essential step for recovering particular plant species of high conservation importance. Furthermore, reducing carp abundance could have ancillary benefits of reducing dominance by invasive plant species. Lastly, where carp cannot be eliminated, managers should target native macrophytes that are relatively tolerant of carp in shoreline plantings and other revegetation efforts.